Pelayanan Ibu Hamil, Melahirkan, Nifas Dan Kontrasepsi Melalui Alarm Tersetting Sejak Awal - Ulumiyah Ulumiyah; Novi Anggraeni; Eny Susanti; Eddy Moeljono; Amriani Amrian (LPPM STIKES Marendeng Majene, 2026)
Efforts to accelerate the reduction of the maternal mortality rate are carried out by ensuring that every mother has access to quality maternal health services, such as prenatal care, delivery assistance by trained health workers at health care facilities, postpartum care for mothers and infants, specialized care and referrals in the event of complications, and family planning services, including postpartum contraception. Continuity of care can be achieved through reminders—which can take the form of a messaging feature or an app—designed to help individuals remember that there is a specific task to be performed on a particular day or at a specific time. The novelty of this study lies in the development of an integrated reminder system designed to support the continuity of maternal care from pregnancy through childbirth, the postpartum period, and contraceptive services. The objective of this study is to analyze the impact of implementing the Kamal Port method on prenatal checkups, choice of delivery facility, postpartum visits, and contraceptive services. The research method used was a quasi-experimental study with a post-test with control group design. The sample consisted of 38 pregnant women in their second and third trimesters in January 2026 at the Ulumiyah-Kamal-Bangkalan Maternal and Child Health Center (TPMB), selected using simple random sampling. Data analysis was performed using bivariate analysis with a t-test. Analysis Results: There were significant differences in the continuity of prenatal care (p=0.000), choice of delivery method (p=0.011), postpartum visits (p=0.004), and contraceptive use (p=0.020) between the group that used alarm reminders to track their prenatal care schedule and the group that did not use alarm reminders.